Preliminary Observation on Leucoma sericea Moore (Lepidoptera : Lymantridae)-a Serious Pest of Parratiopsis Jacquemontiana Decne in Kashmir Forests - Bhat, Mohd. Rafiq (Indian Forester, 1989)
Leucoma sericea Moore (Lepidoptera: Lymantridae) is a serious pest of Parratiopsis Jacquemontiana in Kashmir valley. It grows abundantly in Kashmir forests and is economically very important.